Impaction of tooth 13 type II (Yamamoto Classification) accompanied by recurrent fibromatous epulis with suppurative chronic inflammation: Impkasi gigi 13 tipe II (Klasifikasi Yamamoto) disertai rekuren epulis fibromatosa dengan radang kronik supuratif - Tajrin, A.; Anam, Mukhtar Nur; Yusuf, Muh Rizky Adipratama (Makassar Dental Journal PDGI Makassar, 2025)
Fibromatous epulis is often found in the oral cavity especially on the gingival margin, cheeks and tongue. The aetiology general-ly stems from chronic irritation. This article discusses a series of treatment stages and management of biopsy excision and odon-tectomy of tooth 13, prognosis of treatment of EF with suppurative chronic inflammation. A 23-year-old female came to the de-partment of Oral and Maxillofacial Surgery of RSGMP Hasanuddin University with complaints of a lump on the right maxillary gum since ±8 months ago. The patient had a history of gum lump surgery with the same location ±1 year ago. Intra oral exami-nation: gingival lump of teeth 11-12 with size ±1.6x1.5x0.5 cm with spongy consistency, and pedunculated, media caries of teeth 11, 21, post-endodontic composite filling of tooth 12. OPG and thoracic radiographic examination were performed. In this case, biopsy excision and odontectomy of tooth 13 under general anaesthesia were performed and histopathological examination was performed. It was concluded that biopsy excision and odontectomy of tooth 13 aimed to remove the epulis and prevent recurrence of EF.